Porphyromonas gingivalis affects neutrophil pro-inflammatory activities - Agnieszka Zimny; Alicja Płonczyńska; Alicja Płonczyńska; Wiktor Jakubowski; Natalia Zubrzycka; Natalia Zubrzycka; Jan Potempa; Jan Potempa; Maja Sochalska (Frontiers in Cell and Developmental Biology)
Porphyromonas gingivalis is the primary pathogen responsible for the development of periodontal inflammatory disease. Although gingipains are the major virulence factor of the pathogen, their role in impairing apoptosis and immune cell function is not fully understood. To investigate the impact of gingipains on neutrophil viability and function, we conducted studies using murine HoxB8 neutrophils and primary human neutrophils infected with wild-type strains of Porphyromonas gingivalis (W83 and ATCC 33277), or a gingipains-null mutant with deleted gingipains encoding genes, or wild-type bacteria preincubated with specific gingipain inhibitors. Flow cytometry revealed that wild-type Porphyromonas gingivalis had a marked effect on neutrophil viability regulated by anti-apoptotic proteins belonging to the Bcl-2 family; however, these effects were independent of gingipain expression or activity. Importantly, experiments using primary human neutrophils and macrophages revealed that gingipains play a significant role in the disruption of immune cell functions via the induction of reactive oxygen species and inactivation of neutrophil elastase activity. Additionally, although gingipains played a role in modulating the IL-8-dependent inflammatory response of human neutrophils, they did not affect the expression levels of pro-inflammatory cytokines TNF-α and IL-6.